Julio Cortázar : des débuts en littérature sous le signe de la controverse (1947) - Bobard, Laure (Romanica Silesiana)
In 1947, Julio Cortázar writes “Teoría del túnel,” an essay in which he expresses his desire to overhaul literature, emphasizing the need for the writer, whom he refers to as a “rebel,” to distance himself from certain literary models which he considers fossilised. The essay comes through as an invitation to change one’s writing habits and, at the same time, strive to develop a language capable of depicting man in all his complexity. The following paper demonstrates that El Examen (1950) and Diario de Andrés Fava — a diary initially meant to be part of the novel — are experimental fields that enable the author to explore the possibilities of transgressing the traditional literary codes and implement the proposals he had put forward a few years before in “Teoría del túnel.” Key words: Cortázar, novel, transgression, literary codes.